Synthesis of linear polylactic acid –based urethanes using tin modified closite -30b catalyst - Selukar, Balaji S.; Parwe, Sharad P.; Mohite, Kavita K.; Garnaik, Baijayantimala (Advance Material Letters, 2012)

Synthesis of ciprofloxacin-conjugated poly(L-lactic acid) polymer for nanofiber fabrication and antibacterial evaluation - Parwe, Sharad P.; Chaudhari, Priti N.; Mohite, Kavita K.; Selukar, Balaji S.; Nande, Smita S.; Garnaik, Baijayantimala (International Journal of Nanomedicine, 2014)
Ciprofloxacin was conjugated with polylactide (PLA) via the secondary amine group of the piperazine ring using PLA and 7-(4-(2-Chloroacetyl) piperazin-1-yl)-1-cyclopropyl-6-fluoro-1, 4-dihydro-4-oxoquinoline-3-carboxylic acid. Zinc prolinate, a biocompatible catalyst was synthesized, characterized, and used in ring opening polymerization of L-lactide. Five different kinds of OH-terminated poly(L-lactide) (two-, three-, four-, six-arm, star-shaped) homopolymers were synthesized by ring opening polymerization of L-lactide in the presence of dodecanol, glycerol, pentaerythritol, dipentaerythritol as initiator and zinc prolinate as a catalyst. The structures of the polymers and conjugates were thoroughly characterized by means of gel permeation chromatography, matrix-assisted laser desorption/ionization-time of flight mass spectrometry, and nuclear magnetic resonance spectroscopy. PLA (molecular weight = 100,000) and ciprofloxacin conjugated PLA were used for fabrication of nonwoven nanofiber mat (diameter ranges; 150-400 nm) having pore size (62-102 nm) using electrospinning. The microbiological assessment shows that the release of ciprofloxacin possesses antimicrobial activity. The drug-release behavior of the mat was studied to reveal potential application as a drug delivery system. The result shows that the ciprofloxacin release rates of the PLA conjugate nonwoven nanofiber mat could be controlled by the drug loading content and the release medium. The development of a biodegradable ciprofloxacin system, based on nonwoven nanofiber mat, should be of great interest in drug delivery systems.
Keywords: antibacterial activity; ciprofloxacin conjugated polylactides; CP-PLA; drug release; electrospinning; MDR; nonwoven nanofibers; zinc prolinate

Investigation of the biocompatibility and cytotoxicity associated with ROP initiator and its role in bulk polymerization of L-lactide - Parwe, Sharad P.; Warkad, Shrikant D.; Mane, Manoj V.; Shedage, Pranita S.; Garnaik, Baijayantimala (Polymer, 2017)
Poly (L-lactide) (PLLA) is one of the most attractive polymers for use in biomedical applications. In such applications it is necessary to reduce the use of toxic chemicals and catalysts used in PLLA synthesis, to minimize any adverse effects. In view of this, we have performed ring opening polymerization (ROP) of Llactide (LA) using biocompatible initiator, namely, Zinc L-Proline (ZnP) in bulk. High molecular weight PLLA (Mw up to 1.45 x 10(5) Da) was obtained using the ZnP complex. The ZnP complex is safe, easy to prepare, store and handle. H-1 and C-13 NMR spectra of PLLA were used to determine the extent of monomer conversion and stereo sequence respectively. Differential Scanning Calorimetry (DSC) and Size Exclusion Chromatography (SEC) were used to determine thermal properties, Mn, Mw and polydispersity index respectively. The mechanism of ROP of LA in the presence of ZnP was studied using Density Functional Theory (DFf) which was in good agreement with results from H-1 NMR and Matrix-Assisted Laser Desorption/Ionization Spectrometry (MALDI-TOF). Biocompatibility/non toxicity of PLLA prepared using ZnP was studied in-vitro using MTT assay by examining the proliferation rate of mouse myoblast C2C12 cell line. Escherichia coli and Staphylococcus aureus were used for the study of antibacterial activity of PLLA. (C) 2017 Elsevier Ltd. All rights reserved.